KESALAHAN PENULISAN HURUF HIRAGANA DALAM KARANGAN BERBAHASA JEPANG MAHASISWA PROGRAM STUDI PENDIDIKAN BAHASA JEPANG FKIP UNIVERSITAS RIAU - Jarwati, Nurul Tri; Rahayu, Nana; Budiani, Dini (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2024)
Abstrack: There are 46 hiragana letters fromあ 'a' to ん 'n'. Each letter has certain writing rules called kakijun. Writing hiragana letters according to the rules is very important to produce balanced and readable letters. Errors in writing letters can cause the words written to have a different meaning, or even no meaning at all. This article aims to find out what writing errors there are in Japanese essays by students of the Japanese Language Education Study Program, FKIP, Riau University. This type of research is descriptive qualitative. The subjects of this research were students of the Japanese Language Education Study Program, FKIP, Riau University, class of 2018 and 2019. Research data was obtained from students' written Japanese essays. Research data analysis uses qualitative descriptive analysis methods. The results of the research showed that students of the Japanese Language Education Study Program, FKIP, Riau University made the most errors in writing hiragana letters in the category of errors in writing letters, which were divided into errors in writing dakuon ("), errors in using long sounds (chōon), errors in using yōon ( small ゃ、ゅ、ょ), and errors in the use of sokuon (lower っ); then in the category of mismatches in the form of letters that resemble other letters, the category of errors in selecting letters that are completely different, and in the category of errors in writing hiragana letters that have no shape; letters at all.Keywords: Writing Hiragana Letters, Errors in Writing Letters, Hiragana Letters